Biological Stoichiometry Regulates Toxin Production in Microcystis aeruginosa (UTEX 2385) - Nicole D. Wagner; Felicia S. Osburn; Jingyu Wang; Raegyn B. Taylor; Ashlynn R. Boedecker; C. Kevin Chambliss; Bryan W. Brooks; J. Thad Scott (Toxins, 2019)
Harmful algal blooms (HABs) are increasing in magnitude, frequency, and duration globally. Even though a limited number of phytoplankton species can be toxic, they are becoming one of the greatest water quality threats to public health and ecosystems due to their intrinsic toxicity to humans and the numerous interacting factors that undermine HAB forecasting. Here, we show that the carbon:nitrogen:phosphorus (C:N:P) stoichiometry of a common toxic phytoplankton species, Microcystis, regulates toxin quotas during blooms through a tradeoff between primary and secondary metabolism. Populations with optimal C:N (< 8) and C:P (< 200) cellular stoichiometry consistently produced more toxins than populations exhibiting stoichiometric plasticity. Phosphorus availability in water exerted a strong control on population biomass and C:P stoichiometry, but N availability exerted a stronger control on toxin quotas by regulating population biomass and C:N:P stoichiometry. Microcystin-LR, like many phytoplankton toxins, is an N-rich secondary metabolite with a C:N stoichiometry that is similar to the optimal growth stoichiometry of Microcystis. Thus, N availability relative to P and light provides a dual regulatory mechanism that controls both biomass production and cellular toxin synthesis. Overall, our results provide a quantitative framework for improving forecasting of toxin production during HABs and compelling support for water quality management that limit both N and P inputs from anthropogenic sources.